สื่อสารคดี เพื่อให้ประชาชนในท้องถิ่นอำเภอปาย จังหวัดแม่ฮ่องสอน เกิดความตระหนักถึงการอนุรักษ์แหล่งท่องเที่ยวเชิงนิเวศ - ชมภูราษฎร์, ธีรยา (Community and Social Development Journal, 2012)
งานวิจัยนี้เป็นงานวิจัยกึ่งทดลอง มีวัตถุประสงค์เพื่อผลิตสื่อสารคดีเพื่อให้ประชาชนเกิดความตระหนักถึงการอนุรักษ์แหล่งท่องเที่ยวเชิงนิเวศ โดยการใช้แนวคิดการท่องเที่ยวเชิงนิเวศน์ แนวคิดความตระหนัก ทฤษฎีการสื่อสารเพื่อการโน้มน้าวใจ ทฤษฎีความพึงพอใจ และ ความรู้เกี่ยวกับการผลิตสารคดี ซึ่งใช้เทคนิคการนำเสนอด้านลบ เพื่อให้ได้ผลด้านบวก และหาประสิทธิภาพของสื่อสารคดี ความพึงพอใจหลังรับชมสารคดี กลุ่มตัวอย่างได้แก่ประชาชนในท้องถิ่นที่อาศัยอยู่ในอำเภอปาย และนักท่องเที่ยว เครื่องมือในการวิจัยครั้งนี้ คือ สื่อสารคดีเรื่องเก็บปาย...ไม่ให้เปลี่ยน (ปาย) ไป แบบสอบถามข้อมูลทั่วไป แบบประเมินคุณภาพโดยผู้เชี่ยวชาญและแบบสอบถามความพึงพอใจที่มีต่อสื่อสารคดี สถิติที่ใช้ในการวิเคราะห์ข้อมูลคือ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่าสารคดีสามารถสร้างความตระหนักถึงการอนุรักษ์แหล่งท่องเที่ยว เชิงนิเวศต่อประชาชนในท้องถิ่นที่อาศัยอยู่ในอำเภอปายอยู่ในระดับมาก ส่วนนักท่องเที่ยวอยู่ใน ระดับมาก แสดงให้เห็นว่านักท่องเที่ยวมีความตระหนักมากกว่าประชาชนในท้องถิ่น การพัฒนาสื่อ ให้มีประสิทธิภาพโดยผู้เชี่ยวชาญอยู่ในระดับดี และผลหลังจากชมสารคดีมีระดับความพึงพอใจ ของประชาชนในท้องถิ่นที่อาศัยอยู่ในอำเภอปาย อยู่ในระดับมาก และนักท่องเที่ยวอยู่ในระดับมาก แสดงให้เห็นว่าประชาชนในท้องถิ่นมีความพึงพอใจต่อสารคดีมากกว่านักท่องเที่ยว A Documentary for Local People in Amphur Pai, Mae Hongson Province, for The Realization of Awareness of The Conservation of Eco-Tourism Locations The purpose of this Quasi-Experimental research is to produce a documentary to raise realization of the conservation of eco-tourism locations by utilizing the concept of eco-tourism, awareness, Communication Theory for Persuasion, Contentment Theory and knowledge of documentary production which use the negative representation to achieve a positive result and to find the level of satisfaction after watching the documentary. The sample are local people in Pai and tourists. The tools of the research are the documentary media; Keb Pai...Mai Hai Plean Pai, a questionnaire for general information, the evaluation from the experts and a questionnaire about satisfaction with the documentary. The statistic is analyzed by percentage, average and standard deviation. The result showed that documentary is able to raise realization of the conservation of eco-tourism locations in local people in Pai to a high standard. The awareness of the tourists is also at a high level. It means that the tourists have more awareness than local people. The media development has an efficiency at good level from the experts. And the level of satisfaction after watching the documentary in local people in Pai is high at a level and in the tourists, which means that more local people are satisfied with the documentary than the tourists.